A 2.5 GHz Low Noise Phase Locked Surface Transverse Wave VCO - Fleischmann, Bernd; Roth, Alexander; Russer, Peter; Weigel, Robert (Proc. IEEE Ultrasonics Symposium, 1989, 1989)
A hybrid VCO (voltage-controlled oscillator) at 2.488 GHz which is phase locked to a crystal oscillator operating at 75.4 MHz is described. Acoustic surface transverse wave (STW) delay lines operating at the fifth harmonic are used as the frequency-controlling element of the VCO. In order to reduce the delay-line electromagnetic feedthrough a three-transducer-type STW filter design is combined with a microstrip rat-race coupler. The filters were designed using advanced analysis methods and fabricated on rotated Y-cut quartz substrates with a standard photolithographic process. The delay lines were characterized by a center frequency of 2.49 GHz, an untuned insertion loss of 22 dB, an unloaded Q value of 1280, and a group delay time of 158 ns. The signal of the VCO is mixed with the local (crystal) oscillator signal multiplied by 32, thus providing an IF (intermediate frequency) signal of 75.4 MHz that feeds the phase-locked loop, which has a bandwidth of 300 kHz. A single-sideband phase-noise-to-carrier ratio of -112 dBc/Hz at 1-kHz offset has been attained
–empty–::1512001600,fleischmann1989a
Keywords: acoustic delay lines; phase-locked loops; surface acoustic wave devices; ultrasonic devices; variable-frequency oscillators; 158 ns; Q value; acoustic surface transverse wave delay lines